LELANG MELALUI TROMOL POS 8118 PADA KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG YOGYAKARTA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research is aimed to examine: (1) the legality of the auction implementation which held by the state treasury and auction agency in Yogyakarta.The specific auction would be on 'tromol post' or mail box 8118. The duration of the research would be limited only from 2007 to 22 June 2010